Curriculum of Salaf at Islamic Hight School Futuhiyyah 1 Maranggen, Demak - Syarifah; Isroani, Farida; Defi Firmansah; Hidayah, Khofifatul (AL MURABBI, 2022)
Abstrack Within its framework, the world of education faces a complex problem different, like curriculum changes. As a reaction to the curriculum changes that soccurred in Indonesia and government policies, ought to some The Salaf Boarding school and the Islamic School are to change the method of teaching, the Salafi learning, to the method of modern learning, that is, cooperation between them. In this search a type of field research is used with a descriptive model or feature of the qualitative. Used data collection method note: 1).The observation 2) The interview. 3) The documents to be collected from Futuhiyyah High School 1 Maranggen. And the style data analysis use served analyzing data at Miles and Huberman Three ways, reduce data, data presentation, and conclusion. Results from this search 1) Done Include a curriculum Boarding school predecessor In the 2013 curricula, the local content consists of the internal curriculum, the joint curriculum, and the external methodology, collecting method boarding school The predecessor between learning styles boarding school predecessor and thetechniques learn to talk It uses heritage books for learning 2)Futuhiyyah 1 Mranggen High School advances boarding school curriculum, combines techniques modern learning and traditional methods of the salaf boarding school and the get up teachere religious action evaluation questions to Advances Boarding school Curriculum Independently without government help. The disadvantages of the curriculum of the alaf Boarding school are the lack of focus and understanding of students who do not live in a district The Boarding school The especially to understand the lesson advances boarding school. Keywords: Curriculum, the curriculum of the Salaf Boarding school